Biomarkers of HIV associated malignancies and of drug interaction between anti-retrovirals (ARVs) and chemotherapy - Flepisi, Thabile Brian (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.